Passive Mechanical Properties of Cardiac and Arterial Tissue: A Paired Comparison Study in a Calf Model (University of Denver Undergraduate Research Journal, 2024)
Background: The mechanical behavior of heart tissue plays a crucial role in elucidating cardiac physiology and pathophysiology. Accurate measurement of the mechanical properties of cardiac and arterial tissues is indispensable for advancing computer simulations and developing medical devices. This study aimed to assess the passive mechanical properties of cardiac and arterial tissue in a calf model using a paired comparison method.Methods: A planar biaxial stretching device was used to determine the mechanical characteristics of 84 square specimens obtained from 14 different anatomical regions. Cauchy stress-Green strain curves were constructed for each anatomical area, and a Fung-type constitutive model was applied to fit the raw data. The strain energy and anisotropy index were subsequently calculated.Results: The experimental results indicated that all tissue specimens exhibited nonlinear responses to biaxial stress. Comparison based on the magnitude of the strain energy function revealed that the aorta showed the highest strain energy, followed by the left ventricles, pulmonary artery, right ventricle, left atrium, and right atrium, respectively. Among the different areas, the left ventricle displayed the highest level of tissue anisotropy. These observations align with previous investigations on human heart tissue.Conclusions: We comprehensively characterized the mechanical behavior of various heart chambers and significant arteries using rigorous quantitative analysis. The outcomes of this research provide valuable insights for advancing our understanding of heart physiology and exploring potential therapeutic approaches for cardiovascular diseases.